The financial performance of non financial institution in Malaysia: a case study at Tabung Haji Malaysia / Siti Fatimah Rasdi - Rasdi, Siti Fatimah (2008)
This study investigates the financial performance at Tabung Haji. The period covers from the year 2000 to 2007. the methodology used are liquidity ratios, profitability ratios, common size income statement, comparative analysis and trend analysis to evaluate the financial performance at Tabung Haji Malaysia. From the study, it shows that Tabung Haji has faced a bad financial condition in year 2000. During this year they still recover from the economic crisis that hit Malaysia in 1998. Tabung Haji has shown an improvement from year to year and in the year 2007 has proved that they have achieved their target where it shows a better financial condition.